KEBIJAKAN KURIKULUM PENDIDIKAN AGAMA ISLAM DI INDONESIA - Ayu Ratih Rizki Pradika (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2020)
This writing is motivated by a variety of curriculum changes that have been experienced. So there is an assumption from several parties in the form of 'replace minister for curriculum change'. The curriculum is the effort of educational institutions in planning and organizing goals, content and learning materials along with ways used in an effort to influence students to be able to learn both indoors and outdoors by providing activities under the responsibility of the school to achieve educational goals that are predetermined. This writing aims to determine the nature of the curriculum and know the policies and development of Islamic religious education curriculum in Indonesia, focusing on the development of pre-independence, old order, new order, and reform order curricula (PAI). In the implementation of this study uses a literature approach with descriptive analysis methods. This study found that Islamic religious education experiences dynamics in line with the government's political attitude towards Muslims.